Characteristics and Yield of Modern Approaches for the Diagnosis of Genetic Causes of Kidney Stone Disease - Spasiano, Andrea; Treccani, Mirko; De Tomi, Elisa; Malerba, Giovanni; Gambaro, Giovanni; Ferraro, Pietro (Genes, 2024)
Background: Kidney stone disease (KSD) is characterized by an increasing prevalence worldwide, representing an important clinical issue and a financial burden for healthcare systems. A KSD-causing monogenic variant is traditionally expected in up to 30% of children and 1–5% of adults forming stones, confirmed by a strong connection between a positive family history and KSD. The insufficient use of genetic testing in these patients is associated with a lack of perceived benefit and a scarce awareness of inherited kidney diseases. Genetic testing has important practical implications, such as the possibility of earlier diagnoses, familial counseling, and tailored therapy, based on the evaluation of fine-mapped pathogenic variants. Our aim is to analyze the current evidence on genetic testing in KSD patients to whom genetic tests were applied without strict a priori selection criteria, to provide an overview of its diagnostic yield and factors potentially affecting it (such as the age of KSD onset, a familial history of KSD, consanguinity, and extrarenal features). Methods: A literature review was performed, selecting original articles published in the last 10 years concerning genetic investigations in patients affected by nephrolithiasis or nephrocalcinosis. Available data were subsequently extracted and analyzed. Results: In total, 13 studies on 1675 patients (77% pediatric populations) were included; 333 patients were determined to be affected by a monogenic disorder, with an overall yield of about 20%. The likelihood of a positive genetic finding was much higher in pediatric (26%) than adult populations (8%). Cystinuria was the most common diagnosis in both populations. After the removal of conditions that could be identified with a stone composition analysis or urinary chemistry investigation, the diagnostic yield dropped to 19% among pediatric patients and below 5% for adults. Conclusions: Genetic testing should be considered in KSD pediatric patients and in selected subgroups of adults with suggestive features when a diagnosis is not established after stone examination and blood as well as urine metabolic profiling.